PENGARUH STRATEGIC LEADERSHIP TERHADAP COMPETITIVE ADVANTAGE MELALUI ORGANIZATIONAL CULTURE SEBAGAI VARIABEL INTERVENING - Intan Saridewi (Business Accounting Review, 2015)
This research aimed to analysize the influence of strategic leadership to competitive advantage through organizational culture. By using the primary data questionnaires were distributed to 60 company managers in Surabaya. The data obtained were analyzed by Structural Equation Modeling by using Partial Least Square software to test the hypothesis. The result showed there was positive influence between strategic leardership toward competitive advantage, strategic leadership toward organizational culture, organizational culture towards competitive advantage, but organizational culture was not an intervening variable between strategic leadership and competitive advantage.